Hubungan antara Kejadian Nokturia dan Kualitas Tidur di Kalangan Mahasiswa Kedokteran selama Pandemi Covid-19 - Besut Daryanto; Fathina Zahrani Rahmaniar; Alidha Nur Rakhmani (Jurnal Klinik dan Riset Kesehatan, 2026)
Background: Nocturia is the most common lower urinary tract disease that characterized by waking up to urinate more than once during the main sleep period and its prevalence increases with age. Aim: This study aimed to investigate frequency, bothersome and relation of nocturia with sleep quality during COVID-19 pandemic in medical students Methods: This study used a cross-sectional approach and an analytical observation method by distributing questionnaires. Questions include demographic characteristics, frequencies of nocturia, and bother score related to nocturia Results: Data on 90 individuals eligible for statistical analysis. The average age was 19.24 ± 1.08 years. Overall nocturia prevalence was 38.8% medical students had nocturia. The nocturia rate was 42.2% and 35.56% in men and women, respectively (p = 0.642). The frequency of nocturia per night was 24.4%, 13.3%, and 0.01% (1, 2, and 4 times, respectively). Conclusion: Nocturia is common among medical students, especially men and it is not related with sleep quality.